If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + 1) = 180 Reorder the terms: 6(1 + y) = 180 (1 * 6 + y * 6) = 180 (6 + 6y) = 180 Solving 6 + 6y = 180 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6y = 180 + -6 Combine like terms: 6 + -6 = 0 0 + 6y = 180 + -6 6y = 180 + -6 Combine like terms: 180 + -6 = 174 6y = 174 Divide each side by '6'. y = 29 Simplifying y = 29
| -1+8x=-3x+4(-2+3x) | | .04x+.06(30)=9.8 | | 3(w+6)+2w=-22 | | -8x-8(x-3)=5(x+9)+7 | | 36=3u+6(u-3) | | -9-x=-6(2x+7) | | -5x+4x+20-10x= | | -11=7y+8(y+8) | | -22+6r=-8r-6(1-r) | | 2a+a=-21 | | (750-x)-600-y=3x-y | | 120.08=2808.97(r) | | (2y-80)=(y+9) | | 7(d-3)+6= | | (8x+12)=(10x-24) | | 3x-4+4x+8+x=180 | | (x+30)=(2x) | | 7x-4x+x-4+3x= | | 6.5x-5+x-1.2= | | 4b-6-9b-8= | | 682/d=21 | | (3x-15)=(2x+25) | | -5=5x+5y | | 50(t)=-16t^2+50o | | 50(t)=-16t^2+ho | | h(t)=-16t^2+ho | | 2(-8)-21(-8)-7= | | 25-15(-8)= | | 45=9/2h | | 25-15(8)= | | 45=1/2h(9) | | 2(8)-21(8)-7= |